Insider Deviant Behavior in Cybersecurity - Anti, Emmanuel (Vaasan yliopisto, 2025)
Insider deviant behavior (IDB) in information and cybersecurity is a persistent challenge for organisations and society. Traditional approaches grounded in technocentric, criminological, psychological, and sociological theories provide fragmented explanations that do not fully capture the complexity of insider threats in practice. This dissertation synthesises findings from four research articles to propose a human-centered framework for understanding and mitigating IDBs, emphasising empathy and ethics in cybersecurity. The study maps the theoretical landscape and identifies 46 theories that attempt to explain insider behaviour. These theories remain fragmented across psychological, organisational, sociocultural, and decision-making perspectives. The study critiques their limitations and calls for interdisciplinary integration that accounts for contextual, ethical, and emotional factors. This interdisciplinary approach, which draws from various fields, is crucial for a comprehensive understanding of insider deviant behavior. The dissertation also addresses the disruptive role of artificial intelligence (AI) and how emerging technologies reshape notions of autonomy, justice, surveillance and stress – all of which are linked to insider deviance. As a mitigation strategy, it introduces a design thinking-based framework (DESTIC) built on empathy, collaboration, and iterative problem-solving. This participatory model promotes context-sensitive and ethically grounded security practices. Moving beyond the traditional view of insiders as either rational actors or sociotechnical risks, the study argues for dynamic theoretical models that integrate organisational identity, emotional experience, and technological realities. Although focused primarily on intentional deviance and offering a conceptual application of the proposed framework, it provides a foundation for future interdisciplinary and ethically conscious research relevant to the digital workplace.

Sisätoimijan poikkeava käyttäytyminen (insider deviant behavior, IDB) tieto- ja kyberturvallisuudessa on monimutkainen ja jatkuva haaste organisaatioille ja yhteiskunnalle. Perinteiset teknisiin, kriminologisiin, psykologisiin ja sosiologisiin teorioihin pohjaavat lähestymistavat eivät tavoita sisäuhkien kompleksisuutta käytännön konteksteissa. Tämä väitöskirja kokoaa neljän tutkimusartikkelin löydökset ja esittää ihmiskeskeisen viitekehyksen IDB-ilmiöiden ymmärtämiseksi ja hillitsemiseksi. Tutkimus tunnistaa 46 teoriaa, jotka selittävät sisäpiiriläisten käyttäytymistä, mutta jotka ovat keskenään pirstaleisia psykologisten, organisatoristen, sosiokulttuuristen ja päätöksenteon näkökulmien välillä. Se kritisoi näiden teorioiden rajoituksia ja korostaa monitieteisen lähestymistavan tarvetta, jossa huomioidaan myös kontekstuaaliset, eettiset ja emotionaaliset tekijät. Erityisesti tutkimus tuo esiin käsitteen kognitiivinen poikkeavuus – usein sivuutetun mutta keskeisen sisäpiiriläistoiminnan edeltäjän – ja osoittaa, kuinka ajatukset ja asenteet voivat johtaa poikkeavaan käyttäytymiseen. Tutkimus tarkastelee myös tekoälyn (AI) häiritsevää vaikutusta ja sitä, miten kehittyvät teknologiat muuttavat käsityksiä autonomiasta, oikeudenmukaisuudesta, valvonnasta ja stressistä – tekijöistä, jotka kytkeytyvät IDB-ilmiöihin. Ennalta-ehkäiseväksi strategiaksi väitöskirja ehdottaa muotoiluajatteluun perustuvaa DESTIC-viitekehystä, jossa painottuvat empatia, yhteistyö ja iteratiivinen ongelmanratkaisu. Tämä osallistava malli painottaa kontekstiherkkiä ja eettisesti perusteltuja turvallisuusstrategioita. Tutkimus siirtyy pois perinteisestä näkemyksestä, jossa sisäpiiriläiset nähdään joko täysin rationaalisina toimijoina tai pelkkinä sosioteknisinä riskeinä. Se puolustaa dynaamisia malleja, jotka huomioivat organisatorisen identiteetin, emotionaaliset kokemukset ja teknologiset realiteetit. Vaikka painopiste on tahallisessa poikkeavuudessa ja kehitetty viitekehys esitellään konseptuaalisella tasolla, tutkimus luo perustan tulevalle monitieteiselle, eettisesti tietoiselle ja käytännönläheiselle tutkimukselle digitaalisessa työympäristössä.
Keywords: data systems; data security; information technology; deviant behaviour; organisations (systems); participatory planning; cyber security; information behavior; fi=Informaatiotekniikka|en=Information Technology|